Radiation dose and image quality at high-pitch CT angiography of the aorta: intraindividual and interindividual comparisons with conventional CT angiography - Apfaltrer, Paul; Schönberg, Stefan; Fink, Christian (American journal of roentgenology, 2012)
OBJECTIVE: The objective of our study was to evaluate radiation dose and quantitative image quality parameters at high-pitch CT angiography (CTA) of the aorta compared with conventional CTA. MATERIALS AND METHODS: We studied the examinations of 110 patients (65 men and 45 women; mean age ± SD, 64 ± 15 years) who had undergone CTA of the entire aorta on a second-generation dual-source CT system; 50 examinations were performed in high-pitch mode. The mean arterial attenuation, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and figure of merit (FOM) were calculated for the high-pitch CTA and conventional CTA groups. Radiation exposures were compared. RESULTS: All studies were considered of diagnostic quality. At high-pitch CTA, the mean tube voltage and tube current-exposure time product were 118 ± 7 kV (SD) and 197 ± 78 mAs compared with 120 ± 1 kV and 258 ± 78 mAs, respectively, at conventional CTA (p < 0.05). The mean volume CT dose index, dose-length product, and effective dose were 8.1 ± 2.4 mGy, 561.1 ± 178.6 mGy × cm, and 9.6 ± 3.0 mSv at high-pitch CTA and 18.3 ± 7.7 mGy, 1162.6 ± 480.1 mGy × cm, and 19.8 ± 8.2 mSv at conventional CTA (p < 0.001). Attenuation was similar for both protocols, whereas significantly less contrast medium was injected for high-pitch CTA than for standard-pitch CTA (87.3 ± 16 mL vs 97.9 ± 16 mL, respectively; p < 0.01). The SNR and CNR were significantly lower in the high-pitch CTA examinations (p < 0.01), whereas the FOM was nonsignificantly higher. Twenty patients underwent both high-pitch CTA and conventional CTA, with a 45% reduction in radiation dose (p < 0.001). CONCLUSION: High-pitch CTA of the aorta yields 45-50% reduction of radiation exposure as well as contrast medium savings with maintained vessel attenuation.